Oral Administration of 4-Hydroxy-3-Methoxycinnamaldehyde Attenuates Atopic Dermatitis by Inhibiting T Cell and Keratinocyte Activation. - Hyun-Su Lee; Eun-Ju Choi; Heeri Choi; Kyung-Sik Lee; Hye-Ran Kim; Bo-Ra Na; Min-Sung Kwon; Gil-Saeng Jeong; Hyun Gyu Choi; Eun Young Choi; Chang-Duk Jun (PLoS ONE)
Atopic dermatitis (AD) is a skin condition caused by an imbalance of distinct subsets of T helper cells. Previously, we showed that 4-hydroxy-3-methoxycinnamaldehyde (4H3MC) inhibits T cell activation but does not induce apoptosis. Here, we examined the mechanism underlying the inhibitory effect of 4H3MC on AD both in vivo and in vitro. We sought to test the pharmacological effects of 4H3MC using a mouse model of 2, 4-'2,4-dinitrocholorobenzene' (DNCB)- and mite-induced AD. Also, we determined whether 4H3MC affects T cell differentiation and proliferation. Oral administration of 4H3MC attenuated the symptoms of DNCB- and mite-induced AD, including increased ear thickness, serum IgE levels, immune cell infiltration into inflammatory lesions, and pathogenic cytokine expression in ear tissues. In vitro, 4H3MC blocked T cell differentiation into Th1 and Th2 subtypes, as reflected by suppression of T-bet and GATA3, which are key transcription factors involved in T cell differentiation. In addition, 4H3MC downregulated T cell proliferation during Th1 and Th2 differentiation and keratinocyte activation. Collectively, these findings suggest that 4H3MC ameliorates AD symptoms by modulating the functions of effector T cells and keratinocytes.